Analisis Rasio Likuiditas, Rasio Profitabilitas dan Earning Per Share pada PT. Hanjaya Mandala Sampoerna Tbk di Bursa Efek Indonesia Periode 2014-2017 - Muryati Muryati; Kasiyati Yunita W (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
Analysis of the company's financial statements is needed to determine the company's ability to overcome the company's financial problems and make quick and right decisions. Liquidity ratio analysis is a ratio used to measure a company's ability to meet its short-term obligations. Profitability ratio analysis is a ratio used to measure a company's ability to generate profits derived from sales. Earning Per Share is a form of giving benefits to shareholders from each share owned. This study aims to determine the results of the analysis of the solvency, liquidity, profitability and Earning Per Share ratio of PT. Hanjaya Mandala Sampoerna TBK on the Indonesia Stock Exchange for the period of 2014 - 2017. The data used are secondary data in the form of financial statements of PT. Hanjaya Mandala Sampoerna TBK on the Indonesia Stock Exchange for the period of 2014 - 2017. Liquidity ratios are intended for short-term debt which in this research year can show that PT. HM Sampoerna Tbk is very able to meet these obligations, after that the Profitability Ratio is set aside for company profits which in this research year can generate profits even though its development fluctuates with a downward trend. And the last Earning Per Share which is limited to the price per common stock outstanding in this research year can be seen a nominal stock price split. With this research PT.Hanjaya Mandala Sampoerna, Tbk still needs to improve its asset management as much as possible.